replace the third equation by the sum of itself and -1 times the second equation x-2y-7z=17,-6x+4y+5z=-9,8x+7y=z=-4

Question

replace the third equation by the sum of itself and -1 times the second equation x-2y-7z=17,-6x+4y+5z=-9,8x+7y=z=-4

in progress 0
Autumn 14 mins 2021-10-14T01:01:18+00:00 1 Answer 0

Answers ( )

    0
    2021-10-14T01:02:36+00:00

    Answer:

    14x+3y-6z=5

    Step-by-step explanation:

    x-2y-7z=17 — 1

    -6x+4y+5z=-9 — 2

    8x+7y-z=-4 —3

    -1 times the second equation = -1(-6x+4y+5z=-9)

                                                     = 6x-4y-5z=9  –4

    Now we are given that replace the third equation by the sum of itself and -1 times the second equation

    So, New third equation = 8x+7y-z+6x-4y-5z=-4+9

                                           = 14x+3y-6z=5

    Hence the new third equation is 14x+3y-6z=5

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )